Laboratory Voice Data Entry System - Jeremy L. Praissman; John C. Sutherland (BioTechniques)
We have assembled a system using a personal computer workstation equipped with standard office software, an audio system, speech recognition software and an inexpensive radio-based wireless microphone that permits laboratory workers to enter or modify data while performing other work. Speech recognition permits users to enter data while their hands are holding equipment or they are otherwise unable to operate a keyboard. The wireless microphone allows unencumbered movement around the laboratory without a “tether” that might interfere with equipment or experimental procedures. To evaluate the potential of voice data entry in a laboratory environment, we developed a prototype relational database that records the disposal of radionuclides and/or hazardous chemicals. Current regulations in our laboratory require that each such item being discarded must be inventoried and documents must be prepared that summarize the contents of each container used for disposal. Using voice commands, the user enters items into the database as each is discarded. Subsequently, the program prepares the required documentation.